Effects of experimental conditions on solubility measurements for BCS classification in order to improve the biowaiver guidelines (Brazilian Journal of Pharmaceutical Sciences, 2022)
Among the methods described for determining the solubility, shake-flask is suitable to evaluate the equilibrium solubility according to the BCS. Nevertheless, experimental conditions related to the shake-flask method are not well described. Evaluating the effects of experimental conditions on solubility measurements by shake-flask method is important and contributes in biowaiver decision. For this work, propranolol hydrochloride and nimesulide were used as model compound of high and low solubility, respectively. Equilibrium solubility was evaluated at 37 ºC, 100 rpm during 48 hours in buffer media. Effects of the rotation speed, temperature, substance in excess and aliquot withdrawn were evaluated. Small variations of temperature caused significant differences in the solubility and then this parameter must be controlled. Excess of raw material influenced the results of the nimesulide, then, little excess is recommended. Rotation speed did not cause differences in the equilibrium solubilities, but at 150 rpm the equilibrium was reached faster. Aliquot did not present significant differences, but excessive withdrawn should be avoided. Therefore, the evaluation of equilibrium solubility using shake-flask method must be performed in physiological pH conditions, 37 ± 1 ºC, substance in excess 10% above saturation, 50, 100 or 150 rpm and aliquot withdrawn not more than 10% of the media volume.